Unconjugated free bilirubin in preterm infants - van der Schoor, Lori W.E.; Dijk, Peter H.; Verkade, Henkjan J.; Kamsma, Anna C.J.; Schreuder, Andrea B.; Groen, Henk; Hulzebos, Christian V. (Early human development, 2017)
Hyperbilirubinemia guidelines are based on total serum bilirubin (TSB), in combination with either gestational age (GA) or birth weight (BW), postnatal age and specific risk factors. However, TSB is a poor predictor of bilirubin-induced neurotoxicity (BIND). Free unconjugated bilirubin (UCBfree) and the UCBfree/TSB ratio are more directly related to BIND, but data on their postnatal courses are unknown. To characterize the postnatal courses of UCBfree and UCBfree/TSB ratio, and assess their relationships with clinical characteristics. 72 preterm infants≤32weeks GA, admitted to the University Medical Center Groningen, The Netherlands. During the first postnatal week, bilirubin plasma parameters were analyzed and their relationship with clinical parameters was analyzed. Postnatal changes were analyzed using Generalized Estimating Equations. Data are expressed as medians [ranges]. Less than 10% of the cohort (GA: 29 [26–31] weeks; BW: 1165 [600–1975] g) showed hyperbilirubinemic risk factors. We observed a large variation in UCBfree (27 [1–197] nmol/L), that could partly be explained by postnatal age and gender, but not by other risk factors. Maximal UCBfree levels of 50 [13–197] nmol/L occurred at day 4 and were higher in males. In contrast to TSB, UCBfree/TSB ratios (0.19 [0.01–1.04]) were higher in infants with low GA/BW. UCBfree levels vary considerably in preterm infants, despite a low incidence of hyperbilirubinemic risk factors and similar TSB-based phototherapy treatment. UCBfree could not be predicted by GA or BW, but UCBfree/TSB ratios are highest in the smallest preterms, while they have the lowest TSB levels. •Free unconjugated bilirubin (UCBfree) levels vary considerably in preterm infants, also in absence of clinical risk factors.•Variation in free bilirubin levels cannot be explained by birth weight or gestational age.•The UCBfree/total serum bilirubin ratio is highest in the smalles preterms, whilst having the lowest total serum bilirubin.•Current use of predetermined total serum bilirubin thresholds may be improved by the additional use of UCBfree.